2020
DOI: 10.1002/ijgo.13178
|View full text |Cite
|
Sign up to set email alerts
|

Capillary glucose concentration during oral glucose tolerance test for the diagnosis of gestational diabetes

Abstract: Objective To assess concordance between two point‐of‐care testing (POCT) devices and the standard laboratory method in screening for gestational diabetes mellitus (GDM) in Huesca. Methods Pregnant women who met criteria for an oral glucose tolerance test (OGTT) and attended the laboratory between October 2017 and November 2018 were recruited in this prospective observational study. Glucose was measured in venous (laboratory) and capillary blood (Accu‐Chek or Contour Next glucometers). GDM was diagnosed attendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…(20)(21)(22) So the discrepancy in diagnostic performance might be partly attributed to the negative bias with lab methods rather than positive bias with POC. Generally, studies that compared POC without strict measures to control in-vitro glycolysis, like our study, have reported positive analytical bias, (23,24) high sensitivity and NPV (25)(26)(27)(28)(29) for POC with potential for over-diagnosis. While some studies that religiously applied NACB guidelines have reported negative analytical bias and potential for misdiagnosis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…(20)(21)(22) So the discrepancy in diagnostic performance might be partly attributed to the negative bias with lab methods rather than positive bias with POC. Generally, studies that compared POC without strict measures to control in-vitro glycolysis, like our study, have reported positive analytical bias, (23,24) high sensitivity and NPV (25)(26)(27)(28)(29) for POC with potential for over-diagnosis. While some studies that religiously applied NACB guidelines have reported negative analytical bias and potential for misdiagnosis.…”
Section: Discussionmentioning
confidence: 62%
“…In total 230 pregnant women were included. The age and gestation were 34 (30-37) years and 28 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) weeks respectively. Our hospital serves a large ethnically diverse catchment area.…”
Section: Resultsmentioning
confidence: 99%
“…A recent Swedish study supported continuous use of POCT with the Hemocue device in GDM diagnostics [26]. Another recent study suggested that POCT using Accu-Chek can be used to obtain fasting values and to reduce overall waiting times for patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…14 It was consider the "gold standard" in the diagnosis of GDM. 15 The thresholds Cont... Some authors do not find statistically marked differences throughout the whole period of pregnancy 25 , other authors find decreases 26,27 , and still others find increases in the third trimester.…”
Section: Oral Glucose Tolerance Test (Ogtt)mentioning
confidence: 97%